Data Security and Access Rights Management on Anime Content Management Information System - Hermanus Erwan Bali Loko; Joko Sutopo (Jurnal Indonesia Sosial Teknologi, 2024)
In the increasingly developing digital era, data security and access rights management have become crucial aspects in information systems, especially on platforms that manage specific content such as anime. The Anime Content Management Information System (SIPKA) requires a robust security mechanism to protect user data, content and access rights in order to prevent security threats such as unauthorized access, data theft and content manipulation. This study discusses various methods and technologies that can be applied to improve data security and access rights management in SIPKA. Through literature analysis and case studies, this research found that implementing data encryption, multifactor authentication, and role-based access rights management (RBAC) systems are effective strategies in maintaining data integrity and confidentiality. It is hoped that the results of this research can provide guidance for SIPKA developers and managers in implementing appropriate security policies and technology to ensure the security and operational continuity of the system.